2015
DOI: 10.1159/000381225
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Therapies for Psoriasis Vulgaris: A Systematic Review of Randomized Controlled Trials

Abstract: The purpose of this review was to evaluate the efficacy and safety of acupuncture therapies in the treatment of psoriasis vulgaris. Embase, CENTRAL, PubMed, AMED, CINAHL, CNKI, CQVIP, CBM, and Wanfang databases were searched from inceptions to May 2013 for prospective randomized controlled trials evaluating acupuncture therapies for psoriasis vulgaris. No language limitations were applied. Studies were assessed using the Cochrane risk of bias tool. The primary outcome was Psoriasis Area Severity Index (PASI) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 36 publications
(36 reference statements)
0
45
0
Order By: Relevance
“…As previously reported, acupuncture can reduce the postoperative inflammatory response in patients with lung cancer, thereby reducing postoperative pulmonary complications. Moreover, acupuncture has been found to be effective and safe in the management of a variety of pulmonary diseases . Liu et al found that patients undergoing lung cancer surgery have significantly reduced lung‐related complications after electroacupuncture, and the mechanism might be related to the regulation of inflammatory reactions and a reduction in the proinflammatory factors in plasma by acupuncture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported, acupuncture can reduce the postoperative inflammatory response in patients with lung cancer, thereby reducing postoperative pulmonary complications. Moreover, acupuncture has been found to be effective and safe in the management of a variety of pulmonary diseases . Liu et al found that patients undergoing lung cancer surgery have significantly reduced lung‐related complications after electroacupuncture, and the mechanism might be related to the regulation of inflammatory reactions and a reduction in the proinflammatory factors in plasma by acupuncture.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, acupuncture has been found to be effective and safe in the management of a variety of pulmonary diseases. 18,19 Liu et al 14 found that patients undergoing lung cancer surgery have significantly reduced lung-related complications after electroacupuncture, and the mechanism might be related to the regulation of inflammatory reactions and a reduction in the proinflammatory factors in plasma 13 suggested that transcutaneous electrical acupoint stimulation was beneficial for accelerating postoperative recovery and improving patient prognosis. In the present study, among the 68 patients diagnosed with chronic cough, patients who received acupuncture therapy had significantly higher scores than patients who received no therapy, which is consistent with the findings reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the medical records from Australian clinics has revealed that acupuncture is the most frequent form of complementary medicine use for respiratory disorders (Nik Nabil et al, 2015). A systematic review of 16 RCTs that examined the benefits of acupuncture or other related therapies for treatment of COPD has revealed that acupuncture therapies improved health-related quality of life in patients with mild to severe forms of COPD (Coyle et al, 2014). Despite being associated with improvement in St George's Respiratory Questionnaire score, Medical Research Council's dyspnoea scale, dyspnoea visual analogue scale and greater 6-min walking distance when compared to placebo control, acupuncture therapies reportedly had no additional effects on pulmonary function when compared to either placebo or pharmacotherapy.…”
Section: The Use Of Natural Products and Complementary Medicinesmentioning
confidence: 99%
“…An SR to evaluate the efficacy and safety of acupuncture therapies for psoriasis identified six studies on a diverse range of interventions, such as acupuncture, bloodletting and moxibustion (a form of heat therapy using a preparation of Artemisia leaves) . Conflicting evidence from the highly heterogeneous studies and a global failure to report on health‐related quality of life meant there was insufficient evidence to support the use of acupuncture therapies in the treatment of psoriasis.…”
Section: Other Treatments/interventionsmentioning
confidence: 99%